From 'I Don't Like Mondays' to 'Friday I'm in Love' – Day-of-the-Week Effects in Business Surveys - Jonas Hennrich; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2023)
This study identifies day-of-the-week effects in business surveys using monthly data from the ifo Institute. The odds are higher that companies are more likely to exhibit more pessimistic business expectations for the upcoming months on Mondays and more optimistic expectations at the end of the week. The same holds for the assessment of the current business situation. Firms are more uncertain about their upcoming business development on Mondays and less uncertain on Saturdays. The effects are mainly driven by firms from the service sector and by companies with less than 50 employees. Although statistically significant, the effects are economically rather small.
Keywords: D84; E32; D91; 330; day-of-the-week effect; ifo Business Survey; answering behaviour; expectations; uncertainty